Polymerization Shrinkage, Shrinkage Stress, and Degree of Conversion in Bulk-Fill Resin Composites After Different Photo-Activation Methods - Sara Majidinia; Hossein Bagheri; Shadi Ramezani; Mohammad Jafari Giv; Negin Vatanparast; Fatemeh Namdar (Wolters Kluwer Medknow Publications, 2020)
Introduction: The aim of this study was to evaluate the effect of photo-activation methods on the shrinkage behavior of bulk-fill resin composites. Materials and Methods: Three bulk-fill resin composites (Tetric N-Ceram bulk-fill, Xtra fill, and Filtek flowable) were compared in terms of polymerization shrinkage, shrinkage stress, and degree of conversion (DC). Two curing methods were used: 1) conventional and 2) soft-start curing. Five disk-shaped specimens of each bulk-fill composite were fabricated. The deflection disk method and custom-made linear variable differential transformer (LVDT) device evaluated the dimensional changes during polymerization. Universal testing machine was used to measure shrinkage stress. To evaluate DC, the absorbance peaks were obtained using Fourier Transformation Infrared Spectroscopy (FTIR). Data were analyzed by one-way ANOVA and Tukey test. Results: Tetric N-Ceram bulk-fill (conventional mode) showed the highest polymerization shrinkage rate. Filtek flowable resin composite showed least amount of shrinkage stress and highest DC, while Xtra fill (with conventional curing) showed the highest shrinkage stress. Conclusion: Photo-activation method had no effect on decreasing the polymerization shrinkage except for Tetric N-Ceram; also, polymerization shrinkage stress in Filtek flowable composites with both curing methods was less than other groups. DC was product dependent.